Advance Resistor Value Calculator with MATLAB (International Journal of Engineering and Computer Science, 2015)
This paper about the information on creating a MATLAB application with resistor value calculation program. In this application Graphical User Interface (GUI) for ease to use. It notes the use of color code technique to manually calculate value of resistors. This resistor color code calculator will help to determine the value of axial resistors marked with color bands. It can be used for 3 and 4 band resistors. We can select the colors of the corresponding bands by clicking on them in the table. The resistor will visually show band color choices and display the value of the resistor.